Supported metallocene catalyst, process for its preparation and use

CN122940928APending Publication Date: 2026-10-20SINOCHEM QUANZHOU PETROCHEM CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611184197.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

具体而言,本发明旨在解决传统硅胶载体表面硅羟基对茂金属催化剂的毒化问题,同时改善活性中心在载体孔道内分布不均、传质受限以及聚合过程中活性中心易脱落等缺陷,最终实现催化活性、聚合物颗粒形态及微观结构的协同优化

Benefits of technology

[0023]1)有效钝化载体毒化位点:本发明通过异氰酸酯化学将PLA链共价接枝于硅胶表面,PLA分子层能够有效屏蔽硅胶表面的硅羟基,并抑制了硅胶微孔中残留羟基对茂金属中心的毒化作用,从源头上消除了硅羟基对茂金属活性中心的毒化作用,降低了昂贵助催化剂MAO、MMAO的无效消耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a supported metallocene catalyst, its preparation method, and its application. A modified silica support is used. An intermediate, PLA-urethane-Si(OR)3, is generated by reacting uncapped polylactic acid (PLA) with a silane coupling agent, followed by a condensation reaction with silica gel, resulting in covalent grafting of PLA chains onto the silica gel surface. This invention effectively shields the silanol poisoning sites on the silica gel surface through the PLA graft layer. Simultaneously, MAO or MMAO synergistically interacts with the PLA chains to form a highly metallocene-friendly supported microenvironment, anchoring the active centers to the support surface and significantly shortening the monomer mass transfer path. Compared to unmodified silica-supported catalysts, the catalyst of this invention exhibits over 40% increased activity, a narrow molecular weight distribution of 2-4, and regular polymer particle morphology, smooth surface, and extremely low fine powder content. This catalyst is suitable for ethylene polymerization, with a stable and controllable polymerization process, and shows promising industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of olefin polymerization catalyst technology, specifically relating to a supported metallocene catalyst with polylactic acid grafted onto a modified silica support, its preparation method, and its application. Background Technology

[0002] Metallocene catalysts, as a class of single-active-site catalysts, occupy an increasingly important position in the polyolefin industry due to their extremely high catalytic activity, excellent copolymerization performance, and narrow molecular weight distribution of the resulting polymers. However, homogeneous metallocene catalysts face two major challenges in industrial applications: firstly, when directly used in existing slurry or gas-phase processes, they easily lead to reactor wall adhesion, and the resulting polymer particles have poor morphology and low bulk density; secondly, they require large quantities of expensive methylaluminoxane (MAO) and modified methylaluminoxane (MMAO). To solve these problems, the industry generally adopts the loading technique, which involves loading metallocene catalysts onto inorganic supports (such as silica gel and alumina). The classic loading method involves heat-treating the silica gel support and then directly contacting it with the metallocene compound and MAO or MMAO, so that the active components are loaded onto the surface and pores of the support. While this method achieves some degree of catalyst heterogeneity, it still suffers from the following technical drawbacks: First, the silica gel support surface is rich in silanol groups. These groups not only poison metallocene catalysts, anchoring or even deactivating active sites, but also lead to the consumption of large amounts of expensive MAO and MMAO in the passivation process of the support, rather than for catalyst activation. Second, traditional direct loading methods often result in uneven distribution of active sites deep within the support pores, hindering the diffusion of ethylene monomers into the pores. This not only prolongs the induction period of the polymerization reaction but also easily leads to deterioration of the polymer powder morphology due to mass transfer limitations, producing excessive fine powder and affecting subsequent processing. Furthermore, the bonding force between the active sites and the support is weak, making them prone to detachment during polymerization, causing reactor scaling and compromising the stability of the polymerization system.

[0003] In recent years, studies have attempted to modify supports using ionic liquids or polar polymers to improve the microenvironment of active sites. For example, ionic liquid modification has been shown to "pull" active sites to the support surface, improving mass transfer efficiency. However, ionic liquids are expensive, and their synthesis and anchoring processes are complex. Polylactic acid (PLA), a biodegradable polar polymer, is widely available, but its application in metallocene catalysts is rarely reported. This is mainly because PLA molecules contain end groups with active hydrogen, such as hydroxyl or carboxyl groups. Directly introducing these end groups into the catalytic system would poison the metallocene active sites, leading to catalyst deactivation. Therefore, how to utilize the structural characteristics of PLA to avoid its poisoning effect while leveraging its ability to regulate the catalyst microenvironment has become a pressing technical challenge in this field. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a polylactic acid-grafted modified silica support, its preparation method, and the metallocene catalyst supported thereon. Specifically, this invention aims to solve the problem of poisoning of metallocene catalysts by silanol groups on the surface of traditional silica supports, while improving the defects such as uneven distribution of active centers in the support channels, limited mass transfer, and easy detachment of active centers during polymerization, ultimately achieving synergistic optimization of catalytic activity, polymer particle morphology, and microstructure.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] This invention provides a modified silica support for metallocene catalysts, which is prepared by the following steps:

[0007] (1) Preparation of silanized polylactic acid: Under anhydrous and oxygen-free conditions, polylactic acid (PLA) and a silane coupling agent are reacted in an organic solvent (anhydrous toluene) (40~60℃ for 4~8 hours). During the reaction, the hydroxyl groups at the ends of the PLA molecular chains undergo nucleophilic addition reactions with the silane coupling agent to form urethane bonds, and the carboxyl groups at the ends react with the silane coupling agent to form amide bonds and release carbon dioxide.

[0008] (2) Carrier grafting: The PLA-carbamate-Si(OR)3 intermediate obtained in step (1) is mixed with silica gel that has been dried and pretreated at 80-200℃ to remove surface moisture in an organic solvent (anhydrous toluene). The mixture is heated and stirred to allow it to react fully (react at 80-100℃ for 12-24 hours). This causes the alkoxysilane at the end of the intermediate to undergo a condensation reaction with the silanol groups on the surface of the silica gel, forming covalently linked Si-O-Si bonds, thereby grafting PLA molecules onto the surface of the silica gel.

[0009] (3) Post-processing: After the reaction is completed, the obtained solid product is filtered, Soxhlet extracted and washed and vacuum dried in sequence to remove unreacted physical adsorption impurities and obtain a modified silica gel carrier with surface covalently grafted polylactic acid chains.

[0010] Preferably, in step (1), the polylactic acid is uncapped polylactic acid with a number average molecular weight (Mn) of 5,000 to 20,000.

[0011] Preferably, in step (1), the silane coupling agent is one or more of propyltriethoxysilane, propyltrimethoxysilane, and propyltripropoxysilane.

[0012] Preferably, in step (1), the molar ratio of polylactic acid to silane coupling agent is 1:2.2~2.8.

[0013] Preferably, in step (2), the amount of PLA grafted into the silicone is 5wt%~17wt%, more preferably 8wt%~14wt%, and most preferably 10wt%~12wt%.

[0014] Preferably, in step (3), the detergent used for Soxhlet extraction is dichloromethane or chloroform, and the extraction time is 6-24 hours.

[0015] The present invention also provides a method for preparing a supported metallocene catalyst, comprising the above-mentioned modified silica support and a metallocene compound supported on the support.

[0016] A supported metallocene catalyst is prepared by a method comprising MAO or MMAO supported on a modified silica support and a metallocene compound, and including the following steps: (a) Pre-loading of MAO or MMAO: The modified silica support is dispersed in an organic solvent (anhydrous toluene), MAO or MMAO solution is added, and the reaction is stirred at 40-100°C for 4-10 hours, so that MAO or MMAO is preferentially loaded on the surface and pores of the support to form a modified MAO or MMAO layer; (b) Loading of metallocene: A metallocene compound solution is added to the system of step (a), and the reaction is continued at 40-100°C for 4-10 hours, so that the metallocene compound interacts with the pre-loaded MAO or MMAO to form cationic active centers anchored on the support; (c) Post-treatment: After the reaction is completed, the catalyst is filtered, thoroughly washed with an organic solvent to remove unloaded components, and vacuum dried to obtain the supported metallocene catalyst.

[0017] Preferably, the amount of MAO or MMAO added in step (a) is such that the molar ratio of aluminum in the final catalyst to metal M in the metallocene is 50:1 to 300:1.

[0018] Preferably, the metallocene compound in step (b) is a bridged or non-bridged zirconium or titanium compound selected from one or more of the following: dichlorodicarboxylated zirconium, dichlorozirconium, dimethyldicarboxylated zirconium, dimethyldicarboxylated zirconium, ethylene-bridged diindenyl dichloride, dimethylsilyl-bridged dicyclopentadienyl dichloride, bis(n-butylcyclopentadienyl) dichloride, bis(methylcyclopentadienyl) dichloride, ethylene-bridged di(tetrahydroindenyl) dichloride, dimethylsilyl-bridged (tert-butylamido)(tetramethylcyclopentadienyl) titanium dichloride, and nitrogen-containing heterocyclic monoceramic zirconium.

[0019] This invention further provides an olefin polymerization method, which uses the above-mentioned supported metallocene catalyst to catalyze the olefin polymerization reaction, specifically including:

[0020] Under inert gas protection, the above-mentioned supported metallocene catalyst and olefin monomer are added to a polymerization reactor and reacted for 0.5 to 4 hours at a polymerization temperature of 60 to 110 °C and a polymerization pressure of 0.1 to 5.0 MPa to obtain polyolefin resin.

[0021] Preferably, the olefin monomer is ethylene, and the polymerization method is slurry polymerization.

[0022] Compared with the prior art, the present invention has the following significant advantages:

[0023] 1) Effective passivation of carrier poisoning sites: This invention covalently grafts PLA chains onto the surface of silica gel through isocyanate chemistry. The PLA molecular layer can effectively shield the silanol groups on the surface of silica gel and inhibit the poisoning effect of residual hydroxyl groups in the silica gel micropores on the metallocene centers. This eliminates the poisoning effect of silanol groups on the active centers of metallocene from the source and reduces the ineffective consumption of expensive co-catalysts MAO and MMAO.

[0024] 2) Improved microenvironment and dispersibility of active sites: The grafted PLA chains form a flexible polar interface layer on the silica gel surface. This interface layer can prevent the aggregation of metallocene molecules through physical isolation and stabilize the cationic active sites through the weak interaction between the ester groups and the active sites, thereby increasing the number and stability of active sites and achieving higher catalytic activity.

[0025] 3) Optimized mass transfer process and elimination of induction period: The PLA graft layer anchors the metallocene active centers on the surface and pore regions of the support, significantly shortening the diffusion path of ethylene monomers to the active centers. The polymerization reaction can start up rapidly in a shorter time, the induction period is shortened or even disappears, and the polymerization kinetics are better.

[0026] 4) Improved polymer particle morphology and bulk density: The active centers are firmly anchored to the support through covalent bonds, making them less prone to detachment during polymerization and ensuring perfect replication of the support morphology by the polymer particles. The resulting polymer particles have regular morphology, smooth surfaces, low fine powder content, and high bulk density, exhibiting excellent flowability and processing properties.

[0027] 5) More uniform polymer microstructure: Thanks to the stable and uniform single-center catalytic microenvironment provided by the PLA interface layer, the resulting polymer has a narrower molecular weight distribution (Mw / Mn can be as low as 2~4), which can meet the stringent performance requirements of high-end polyolefin materials.

[0028] 6) Stable and controllable polymerization process: The catalyst of this invention exhibits good operational stability in the polymerization reaction, and there is no wall adhesion or scaling in the reactor. It is suitable for existing slurry process industrial equipment and has good prospects for industrial application.

[0029] In summary, this invention successfully constructs a polymer interface that is friendly to metallocene catalysts by chemically grafting PLA onto a silica support, solving the long-standing technical problems in existing supported technologies such as easy deactivation of active centers, limited mass transfer, and poor polymer morphology, and has good prospects for industrial application. Attached Figure Description

[0030] Figure 1 Thermogravimetric curves of silica gel (blue) and PLA-modified silica gel (red);

[0031] Figure 2 The image shows the electron micrograph of the modified silica gel carrier in Example 1a.

[0032] Figure 3 The image shows the electron micrograph of the catalyst prepared in Example 1a. Detailed Implementation

[0033] To make the above-mentioned features and advantages of the present invention more apparent and understandable, specific embodiments are described below in detail. Unless otherwise specified, the methods of the present invention are conventional methods in the art.

[0034] Example 1a

[0035] (1) Under anhydrous and oxygen-free conditions, 5.0 g of uncapped polylactic acid (PLA, PDI < 2.0) with a number average molecular weight of 10,000 was added to a dry 250 mL Schlenk flask, and the mixture was purged with nitrogen three times. 50 mL of anhydrous toluene was added, and the mixture was stirred and dissolved at 50 °C. After the PLA was completely dissolved, 0.31 mL (approximately 1.25 mmol) of propyltriethoxysilane 3-isocyanate (ICPTES, PLA to ICPTES molar ratio 1:2.5) was added, along with one drop of dibutyltin dilaurate (DBTDL) as a catalyst. The mixture was heated to 60 °C and stirred for 8 hours. During the reaction, the terminal hydroxyl and carboxyl groups of PLA reacted with ICPTES to form urethane and amide bonds, respectively, releasing carbon dioxide. After the reaction was complete, the mixture was cooled to room temperature, and the reaction solution was slowly added dropwise to 500 mL of ice-cold anhydrous methanol to precipitate a white solid. The mixture was filtered, washed three times with cold methanol, and the resulting solid was dried under vacuum at 40°C for 12 hours to obtain a polylactic acid intermediate with a terminal triethoxysilyl group, denoted as PLA-Si(OEt)3.

[0036] (2) Take 5.0 g of silica gel (Grace Davison 955 type, average pore size 10 nm, specific surface area 300 m²). 2 / g (dried under vacuum at 200℃ for 12 hours before use) was placed in a dry 250 mL Schlenk flask, and 50 mL of anhydrous toluene was added. The mixture was stirred and dispersed evenly. The intermediate PLA-Si(OEt)3 obtained in step (1) (mass ratio of silica gel to PLA-Si(OEt)3 is 1:0.21) was dissolved in 50 mL of anhydrous toluene and added to the reaction flask. The temperature was raised to 90℃ and the reaction was stirred for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the solid was collected. The solid was placed in a Soxhlet extractor and extracted by reflux for 24 hours with chloroform as the extractant to remove physically adsorbed PLA-Si(OEt)3 and unreacted small molecule impurities. After the extraction was completed, the solid was taken out, washed twice with anhydrous methanol, and then washed once with anhydrous n-hexane. The solid was dried under vacuum at 40℃ to constant weight to obtain a modified silica gel carrier with surface covalently grafted polylactic acid chains, denoted as SiO2-PLA. Thermogravimetric analysis (TGA): Measured under a nitrogen atmosphere, the weight loss rate in the range of 250~400℃ was 11.2 wt%, indicating that the modified PLA grafting amount was approximately 11 wt%.

[0037] (3) Under nitrogen protection, 2.0 g of the above SiO2-PLA support was placed in a dry 100 mL Schlenk flask, and 20 mL of anhydrous toluene was added. The mixture was stirred and dispersed into a uniform slurry. 4.5 mL of a toluene solution (10 wt%) of methylaluminoxane (MAO) was added based on an Al to Zr molar ratio of 200:1. The mixture was stirred at 50 °C for 4 hours to allow MAO to be preferentially loaded onto the surface of the modified silica support. Then, 5 mL of a toluene solution containing 0.10 g of bis(n-butylcyclopentadienyl)zirconium dichloride ((nBuCp)2ZrCl2) was added, and the mixture was stirred at 50 °C for another 8 hours to allow the metallocene compound to interact with the pre-loaded MAO, forming cationic active centers anchored on the support. After the reaction was complete, the mixture was filtered, washed three times with anhydrous toluene, and then once with anhydrous n-hexane. The solid was dried under vacuum at 40 °C to constant weight to obtain a supported metallocene catalyst with a Zr content of 0.45 wt%, denoted as Cat-1a.

[0038] (4) Under nitrogen protection, 150 mL of purified toluene, 0.1 mmol of triethylaluminum as a scavenger, and 5 mg of the above-mentioned Cat-1a catalyst were added sequentially to a 1 L stainless steel high-pressure reactor. The temperature was raised to 70 °C, ethylene was introduced to maintain a pressure of 3.0 MPa, and the reaction was stirred for 1 h. After polymerization, the pressure was released, the reactor was cooled, and the polymer was discharged. The reaction was terminated by ethanol acidification, filtered, washed three times with ethanol, and vacuum dried at 70 °C to constant weight to obtain 37.4 g of polyethylene resin. The catalytic activity was calculated to be 7482 g / g cat. Polymer performance test results: weight average molecular weight (Mw) 41 × 10⁻⁶ 4The molecular weight distribution (Mw / Mn) is 2.3. The polymer particles are regularly spherical with smooth surfaces and no fine powder.

[0039] Example 1b

[0040] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the number-average molecular weight of PLA was changed to 3000. Catalyst Cat-1b was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 1.

[0041] Example 1c

[0042] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the number-average molecular weight of PLA was changed to 5000. Catalyst Cat-1c was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 1.

[0043] Example 1d

[0044] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the number-average molecular weight of PLA was changed to 15,000. Catalyst Cat-1d was prepared according to the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 1.

[0045] Example 1e

[0046] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the number-average molecular weight of PLA was changed to 20,000. Catalyst Cat-1e was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 1.

[0047] Table 1. Effects of PLA with different number-average molecular weights on catalyst activity, molecular weight, and molecular weight distribution.

[0048]

[0049] The results show that, when the PLA grafting amount is the same, molecular weight has a decisive influence on catalyst performance. Too low a molecular weight (3000) leads to excessively high grafting density and a rigid interfacial layer; too high a molecular weight (20,000) leads to excessively low grafting density and insufficient silanol shielding. When the PLA molecular weight is 10,000, the grafting density and chain length reach the optimal balance, forming an ideal flexible interfacial layer, resulting in the best catalytic activity, the narrowest molecular weight distribution, and the highest polymer molecular weight.

[0050] Example 1f

[0051] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the grafting amount of modified PLA was changed to 5 wt%. Catalyst Cat-1f was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 2.

[0052] Example 1g

[0053] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the grafting amount of modified PLA was changed to 8 wt%. Catalyst Cat-1g was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 2.

[0054] Example 1h

[0055] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the grafting amount of modified PLA was changed to 14 wt%. Catalyst Cat-1h was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 2.

[0056] Example 1i

[0057] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the grafting amount of modified PLA was changed to 17 wt%. Catalyst Cat-1i was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 2.

[0058] Table 2. Effects of different modified PLA grafting amounts on catalyst activity, molecular weight, and molecular weight distribution.

[0059]

[0060] Table 2 shows that the amount of PLA grafting has a significant impact on catalyst performance. When the grafting amount is 5 wt%, the PLA layer is too thin, resulting in insufficient silanol shielding, relatively low catalytic activity, and a relatively wide molecular weight distribution. When the grafting amount increases to 11 wt%, the PLA layer uniformly covers the silica gel surface while maintaining unobstructed pores, achieving peak catalytic activity (7482 g / g cat) and the narrowest molecular weight distribution (PDI=2.3). Further increasing the grafting amount to 17 wt% causes PLA chains to block the pores, hindering mass transfer and significantly reducing catalytic activity. Therefore, the preferred PLA grafting amount in this invention is 5~15 wt%, more preferably 8~14 wt%, and most preferably 10~12 wt%.

[0061] Example 1j

[0062] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the metallocene compound was replaced with bis(methylcyclopentadienyl)zirconium dichloride. Catalyst Cat-1j was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0063] Example 1k

[0064] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the metallocene compound was replaced with rac-ethylene bis(1-indenyl)zirconium dichloride. Catalyst Cat-1k was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0065] Example 11

[0066] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that the metallocene compound was replaced with dichlorotitanene. Catalyst Cat-1l was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0067] Example 1m

[0068] The catalyst for olefin polymerization was prepared using the same method as in Example 1a, except that the metallocene compound was replaced with an N-containing heterocyclic zirconium monoxide.

[0069] Catalyst Cat-1m was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0070] The preparation method of N-heterocyclic monocerozirconium in Example 1m includes the following steps:

[0071] In a dry round-bottom flask, 0.1 mol of 2-methylindene, 100 mL of chloroform, 0.105 mol of NBS, and 0.0002 mol of AIBN were added, and the mixture was heated to 61 °C and refluxed for 4 h. The mixture was cooled to room temperature and filtered to remove the succinimide generated in the reaction. The filtrate was washed successively with 50 mL of water, saturated sodium bicarbonate solution, and saturated brine. The organic phase was separated and dried with 20 g of anhydrous sodium sulfate. The solvent was removed by rotary evaporation to obtain the crude product, which was then separated by column chromatography with a hexane:ethyl acetate ratio of 5:1 (v / v) to obtain the product 2-bromomethylindene.

[0072] 0.1 mol of 2-bromomethylindene and 0.11 mol of triphenylphosphine were added to a flask and dissolved in 100 mL of chloroform. The mixture was heated to 61 °C and refluxed for 4 h. After the reaction was complete, the mixture was cooled to room temperature, and 150 mL of diethyl ether was added to precipitate the phosphonium salt. The crude product was purified by recrystallization from 100 mL of dichloromethane. In a round-bottom flask, 0.1 mol of the phosphonium salt prepared above, a magnetic stir bar, 100 mL of dichloromethane, and 0.105 mol of indole-7-carboxaldehyde were added and stirred until dissolved. Under vigorous stirring, 100 mL of sodium hydroxide aqueous solution (50% w / w) was slowly added. The mixture was stirred vigorously at room temperature for 5 h, and then the mixture was transferred to a separatory funnel. The layers were allowed to stand and separated, and the lower organic phase was separated. The aqueous phase was extracted once with 20 mL of dichloromethane, and the organic phases were combined. The organic phase was washed once with saturated brine (50 mL) and then dried over 20 g of anhydrous sodium sulfate (Na₂SO₄). The sodium sulfate was removed by filtration, and the solvent was removed by rotary evaporation to obtain the crude product. The crude product was recrystallized from 50 mL of anhydrous ethanol to obtain intermediate 1.

[0073] Add a magnetic stir bar to a double-necked round-bottom flask, then add intermediate 1 (0.1 mol). Evacuate the system using a vacuum pump, then purge with nitrogen three times to replace the air. Under nitrogen protection, add 100 mL of methanol and Pt / C catalyst (10% of the substrate mass). Using a 1 μL microsyringe, add one drop of thiophene to the system. Replace the gas in the flask with hydrogen. GC analysis showed complete conversion of the starting material (exocyclic double bonds), and the reaction was immediately terminated. Line a Buchner funnel with diatomaceous earth, filter to remove insoluble matter, collect the filtrate, evaporate the solvent to dryness using a rotary evaporator to obtain the crude product, and recrystallize from 35 mL of ethyl acetate to obtain intermediate 2.

[0074] The reaction flask was purged with nitrogen three times. Under nitrogen protection, 100 mL of anhydrous tetrahydrofuran was added, and the system was cooled to -78 °C. 63 mL of a 1.6 M n-butyllithium solution in hexane was slowly added dropwise. 50 mL of a tetrahydrofuran solution containing intermediate 2 (0.05 mol) was added dropwise to the above system, and the reaction was allowed to proceed for 4 h to obtain an indenyllithium solution. In another reaction flask, 0.05 mol of zirconium tetrachloride was suspended in 50 mL of anhydrous toluene. The indenyllithium solution was added dropwise to the above system at -78 °C. After the addition was complete, the temperature was slowly raised to room temperature, and the reaction was allowed to proceed for 24 h. Insoluble matter was removed by filtration, and all solvent was removed by rotary evaporation. Recrystallization was performed using 50 mL of a hexane / toluene mixture (volume ratio 1:1) to obtain an N-heterocyclic monocerocene product (yellow solid) in 72% yield.

[0075] NMR characterization of N-heterocyclic monocerozirconium: ¹H NMR (400 MHz, CDCl₃) δ 7.95 (d, J = 7.9 Hz, ¹H), 7.73 (d, J = 2.7 Hz, ¹H), 7.29-7.67 (m, 6H), 6.33-6.39 (m, 2H), 3.98 (s, ¹H), 2.53-2.72 (m, 2H), 2.29-2.44 (m, 2H). ¹³C NMR (101 MHz, CDCl₃) δ 147.1, 136.1, 135.7, 134.8, 130.9, 130.5, 129.7, 128.6, 128.2, 127.6, 127.3. 126.0, 124.0, 123.3, 118.5, 105.6, 57.0, 39.8, 30.5.

[0076] Table 3. Effects of different metallocene compounds on catalyst activity, molecular weight, and molecular weight distribution.

[0077]

[0078] As shown in Table 3, the polylactic acid grafted modified silica support of the present invention has a good synergistic effect with dizirconia, dititanium, and nitrogen-containing heterocyclic monozirconia compounds, and can obtain polymers with high catalytic activity and narrow molecular weight distribution.

[0079] Comparative Example 2a

[0080] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that unmodified silica gel was used directly as the catalyst support. Catalyst Cat-2a was prepared according to the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0081] Comparative Example 2j

[0082] Catalysts for olefin polymerization were prepared using the same method as in Example 1j, except that unmodified silica gel was used directly as the catalyst support. Catalyst Cat-2j was prepared according to the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0083] Comparative Example 2k

[0084] Catalysts for olefin polymerization were prepared using the same method as in Example 1k, except that unmodified silica gel was used directly as the catalyst support. Catalyst Cat-2k was prepared according to the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0085] Comparative Example 2l

[0086] Catalysts for olefin polymerization were prepared using the same method as in Example 11, except that unmodified silica gel was used directly as the catalyst support. Catalyst Cat-2l was prepared according to the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0087] Comparative Example 2m

[0088] Catalysts for olefin polymerization were prepared using the same method as in Example 1m, except that unmodified silica gel was used directly as the catalyst support. Catalyst Cat-2m was prepared according to the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 3.

[0089] Comparative Example 3a

[0090] Catalysts for olefin polymerization were prepared using the same method as in Example 1a, except that PLA was directly physically mixed with silica gel without the use of a silane coupling agent to modify it. Catalyst Cat-3a was prepared using the same process, and ethylene polymerization was carried out under the same polymerization conditions. The results are listed in Table 4.

[0091] Table 4

[0092]

[0093] As shown in Table 4, when using unmodified silica gel as a support, the catalytic activity of all metallocene compounds was significantly lower than that of the corresponding modified catalysts in the embodiments of this invention. Taking bis(n-butylcyclopentadienyl)zirconia dichloride as an example, the activity of the unmodified catalyst was only 3509 g / g cat, while the activity of the modified catalyst of this invention reached 7482 g / g cat, an increase of 2 times. At the same time, the molecular weight distribution of the polymer obtained by the unmodified catalyst was significantly broadened (PDI ≥ 3.2), and the particle morphology was irregular with more fine powder, indicating that the silanol groups on the surface of silica gel had a serious poisoning effect on the metallocene active centers, and the active centers were easily detached during polymerization. In contrast, this invention effectively shielded the silanol groups and stabilized the active centers through polylactic acid covalent graft modification, thereby achieving a comprehensive improvement in catalytic performance and polymer performance.

[0094] As can be seen from the above embodiments and comparative examples, the polylactic acid-grafted modified silica support provided by the present invention effectively shields the poisoning effect of silanol groups on the metallocene active centers by covalently grafting PLA onto the silica surface, while simultaneously forming a metallocene-friendly polar microenvironment. When the PLA grafting amount is controlled at 10-12 wt% and the PLA molecular weight is 10,000, the catalyst performance reaches its optimal level: the catalytic activity is as high as 7482 g / g cat, the molecular weight distribution is as narrow as 2.3, and the particle morphology is regular and smooth. Compared with the unmodified silica supported catalyst, the activity is increased by more than 100%, and the molecular weight distribution is significantly narrowed. The technical solution of the present invention has significant inventiveness and industrial application value.

[0095] Table 5. EDS elemental analysis of C, Si, and O in silica gel and modified silica gel.

[0096]

[0097] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A supported metallocene catalyst, characterized in that, It includes a modified silica carrier, and methylaluminoxane MAO or modified methylaluminoxane MMAO and metallocene compounds sequentially loaded on the carrier; The surface of the modified silica carrier is covalently grafted with polylactic acid chains of number average molecular weight of 5,000 to 20,000 by a silane coupling agent; the amount of polylactic acid grafted onto the modified silica carrier is 5 wt% to 17 wt%.

2. The supported metallocene catalyst according to claim 1, characterized in that, The polylactic acid is uncapped polylactic acid, and the grafting is achieved by reacting the terminal hydroxyl / carboxyl groups of polylactic acid with a silane coupling agent to form urethane / amide bonds.

3. The supported metallocene catalyst according to claim 1, characterized in that, The silane coupling agent is one or more of propyltriethoxysilane, propyltrimethoxysilane, and propyltripropoxysilane.

4. The supported metallocene catalyst according to claim 1, characterized in that, The metallocene compound is a bridged or non-bridged zirconium or titanium compound selected from one or more of the following: dichlorodicarboxytitanium, dichlorozirconium, dimethyldicarboxytitanium, dimethylzirconium, ethylene-bridged diindene dichloride, dimethylsilyl-bridged dicyclopentadienyl dichloride, bis(n-butylcyclopentadienyl) dichloride, bis(methylcyclopentadienyl) dichloride, ethylene-bridged di(tetrahydroindene) dichloride, dimethylsilyl-bridged (tert-butylamido)(tetramethylcyclopentadienyl)titanium dichloride, and nitrogen-containing heterocyclic monoceramic zirconium.

5. The supported metallocene catalyst according to claim 1, characterized in that, The preparation method of the modified silica carrier includes the following steps: (1) Uncapped polylactic acid with a number average molecular weight of 5000~20000 is reacted with a silane coupling agent in anhydrous toluene at a molar ratio of 1:2.2~2.8 for 4~8 hours at 40~60℃ to generate intermediate PLA-Si(OR)3; (2) The intermediate PLA-Si(OR)3 obtained in step (1) is reacted with silica gel in anhydrous toluene at 80~100 °C for 12~24 hours to graft the intermediate onto the silica gel surface; (3) Extract the product obtained in step (2) with dichloromethane or chloroform for 6 to 24 hours, and dry it under vacuum to obtain the modified silica gel carrier.

6. The method for preparing the supported metallocene catalyst according to claim 1, characterized in that, Includes the following steps: 1) Disperse the modified silica gel carrier in anhydrous toluene, add MAO or MMAO solution, and stir at 40~100 ℃ for 4~10 hours; 2) Add a metallocene compound solution to the system in step 1), and continue stirring the reaction at 40~100℃ for 4~10 hours; 3) Filter, wash, and vacuum dry to obtain the supported metallocene catalyst.

7. The application of the supported metallocene catalyst according to claim 1 in olefin polymerization, characterized in that, Catalytic polymerization of ethylene under conditions of 60~110℃ and 1.0~5.0 MPa.